69. Implementation of a Pharmacist-Driven Blood Culture Communication Process in a Non-Profit Community Hospital. (4th December 2021) - Thumann, Alexis; Williams, Jennifer; Bernabe, Megan; Hankewich, Jillien
Abstract: Background: Rapid diagnostic testing allows for faster identification of culture results and quicker time to targeted antimicrobial therapy. For this to be effective, however, the clinician needs to understand its capabilities and limitations. Pharmacists are well-positioned to assist providers in interpreting rapid diagnostic test results and in the selection of optimal antimicrobial therapy. This study aims to determine if implementing a process in which pharmacists communicate positive blood culture and rapid diagnostic test results improves time to optimal antimicrobial therapy in a community-based hospital. Methods: In November 2020, Mercy Medical Center implemented a new process in which positive blood culture and rapid diagnostic test results are communicated to a pharmacist instead of a nurse on the patient care unit. The pharmacist is responsible for interpreting the results, assessing patient information, and providing the culture results along with drug therapy recommendations to the appropriate licensed independent practitioner. This study was a single-center, pre-post, quasi-experimental study (Pre: November 2019-March 2020; Post: November 2020-March 2021). The electronic medical record was used to identify admitted patients 18 years and older with positive blood cultures in which treatment was provided. Time from culture positivity to optimal antimicrobial therapy was collected and compared pre-post intervention. Secondary outcomes included hospital length of stay and mortality. Results: A total of 480 patients were identified during the study period, of which 247 met inclusion criteria (n = 125 in 2019-2020; n = 122 in 2020-2021) with comparable baseline characteristics. There was no statistical difference in time to appropriate therapy between the groups (p = 0.796). Time to optimal therapy was 6.12 hours shorter in the post-intervention cohort (p = 0.0492). No difference was found for both secondary outcomes of hospital length of stay and inpatient mortality (p = 0.2958, p = 0.096, respectively). Conclusion: A pharmacist-led blood culture communication process improved the care of hospitalized patients in a non-academic, community-based hospital by shortening time to optimal antimicrobial therapy. Disclosures: All Authors : No reported disclosures